Human CD4+ T-Cells: A Role for Low-Affinity Fc Receptors - Chauhan, Anil K. (Frontiers in Immunology, 2016)
Both lymphoid and myeloid cells express Fc-receptors (FcRs). Low affinity FcRs engage circulating immune complexes, which results in the cellular activation and proinflammatory cytokine production. FcRs participate in the internalization, transport and/or recycling of antibodies and antigens. Cytosolic FcRs also route these proteins to proteasomes and antigen presentation pathways. Non-activated CD4+ T-cells do not express FcRs. Once activated, naïve CD4+ T-cells express FcγRIIIa, which upon IC ligation, provide a co-stimulatory signal for the differentiation of these cells into effector cell population. FcγRIIIa present on CD4+ T-cell membrane could internalize nucleic acid containing ICs and elicit a cross-talk with toll-like receptors. FcγRIIIa common γ-chain forms a heterodimer with the ζ-chain of T-cell receptor complex, suggesting a synergistic role for these receptors. This review first summarizes our current understanding of FcRs on CD4+ T-cells. Thereafter, I will attempt to correlate the findings from the recent literature on FcRs and propose a role for these receptors in modulating adaptive immune responses via TLR signaling, nucleic acid sensing and epigenetic changes in CD4+ T-cells.